2019
DOI: 10.3390/environments6060059
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Assessment of Eco-Safe Rural Roads in Panchase Geographic Region in Central–Western Nepal Hills

Abstract: Rural roads are important for the communities in the hilly areas of Nepal as they introduce livelihood opportunities at the local level, and provide better access to the healthcare, education, and resources. Yet, most of the rural roads in Nepal are unplanned and non-engineered, and these roads are often closed for many months during and after the monsoon. Such roads require huge investments, especially post-monsoon, to clear debris and to keep them operational. In parallel, there is evidence that such roads l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…(2012), Shen et al. (2007), Devkota et al. (2019), Pham and Kim (2019) and Inti and Tandon (2021), seven items for the environmental dimension from Shi et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2012), Shen et al. (2007), Devkota et al. (2019), Pham and Kim (2019) and Inti and Tandon (2021), seven items for the environmental dimension from Shi et al.…”
Section: Methodsmentioning
confidence: 99%
“…The first section of the questionnaire contains three scales measuring the constructs of the conceptual model. Resources, managerial and regulatory barriers to the implementation of sustainability practices in HRC projects were measured with a 21-item scale adapted from various sources, namely Pitt et al Devkota et al (2019). For all those constructs, the respondents were required to indicate their level of agreement with a total of 21 items on a 5-point scale ranging from "strongly disagree" (1) to "strongly agree" (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-related hazards are most often driven by intense and/or prolonged rainfall whilst moderated by site-specific basin characteristics (Devkota et al, 2014; Kirschbaum et al, 2012). The critical analysis also found that there were many publications focused on the distribution of landslide events and the thematic grouping of different types of mass movements in which flooding did not feature (Chen et al, 2016; Galli et al, 2008).…”
Section: Bibliometric Analysis and Interpretationmentioning
confidence: 99%
“…In the process of human engineering activities, a large number of slopes are usually excavated [1][2][3]. The formation of cut slopes causes great disturbance to the ecosystem, such as the removal of natural soil, the destruction of natural vegetation and the degradation of biodiversity in mountainous areas [4][5][6]. Such disturbance is increased by additive effects in high altitude areas with a long sunshine duration, an extremely low temperature, constantly changing weather conditions, and concentrated rainfall.…”
Section: Introductionmentioning
confidence: 99%